The cat who wanted to go home - Tomlinson, Jill.; Cole, Joanne (London : Egmont., 2014)
One day, Suzy found a huge basket in a field. She climbed in, settled in the shade under a stool, and was soon fast asleep. When she woke up, the basket was in the sky! Suzy, the little French cat, has found herself in a hot-air balloon on its way to England! This is the start of Suzy's big adventure as she tries to make her way back home to France. In this beautifully illustrated picture book, Jill Tomlinson's heartwarming story has been carefully edited to retain all her gently humorous style, while Paul Howard's lovely pastel images perfectly capture the spirit of this absorbing tale.
O
b
b